2013
DOI: 10.1002/anie.201307464
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Total Synthesis of N‐Methylwelwitindolinone D Isonitrile

Abstract: We report the enantiospecific total synthesis of N-methylwelwitindolinone D isonitrile. Our route features a double C-H functionalization event involving a keto oxindole substrate to introduce the tetrahydrofuran ring of the natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…[2] Except welwitindolinone A ( 4 ), all welwitindolinones isolated to date are 3,4-disubstituted oxindoles with a signature bicyclo[4.3.1]decane core motif, [1, 3] which has captivated considerable interest from the synthetic chemistry community worldwide that resulted in several total chemical syntheses of this family of molecules. [4] …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2] Except welwitindolinone A ( 4 ), all welwitindolinones isolated to date are 3,4-disubstituted oxindoles with a signature bicyclo[4.3.1]decane core motif, [1, 3] which has captivated considerable interest from the synthetic chemistry community worldwide that resulted in several total chemical syntheses of this family of molecules. [4] …”
mentioning
confidence: 99%
“…[1] More recently, Baran and coworkers demonstrated that 4 could be readily obtained by a XeF 2 -mediated oxidative ring contraction of 12- epi -fischerindole I ( 7 ), [4c] which is implicated as the direct biosynthetic precursor to 4 . However, no genes or proteins associated with welwitindolinone biosynthesis have been identified and characterized to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, hydrolysis of 282, followed by IBX oxidation, generated the oxindole intermediate amino- et al (see above) made possible the synthesis of (+)-N-methylwelwitindolinone D isonitrile 296. 48,55 The important intermediate indole 275 (Scheme 49) was at this point converted to oxindole 286 using a one-pot oxidation/hydrolysis sequence (Scheme 52). Since the acidic conditions led to desilylation, reprotection of the alcohol was necessary to provide TBS-protected indole 287.…”
Section: Synthesis Of (-)-N-methylwelwitindolinone C Isothiocyanatementioning
confidence: 99%
“…Related (C-3)-peroxy compounds were observed in previous studies by the Garg and Wood research groups. 55 In order to complete the total synthesis, it remained to elaborate the cyclic carbamate to the ketone and isonitrile functional groups present in the target molecule 296 (Scheme 54). To this end, ketone 292 was reduced to the corresponding alcohol 293 with LiAlH 4 .…”
Section: Synthesis Of (-)-N-methylwelwitindolinone C Isothiocyanatementioning
confidence: 99%